Site selection for hydrogen underground storage using interval type-2 hesitant fuzzy sets - Deveci, Muhammet (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This study presents an interval type-2 hesitant fuzzy set (IT2HFS) based multi-criteria decision making (MCDM) method for selecting hydrogen underground storage sites in Turkey. The proposed method is utilized in a case study that aims to determine the best site among three alternatives. The results show that the proposed method can effectively and flexibly handle the interval type-2 hesitant fuzzy MCDM site selection problems. Finally, the sensitivity analysis is also demonstrated for the proposed method. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen underground storage; Site selection; Interval type-2 fuzzy sets; Hesitant fuzzy sets; Multi-criteria decision making; CRITERIA DECISION-MAKING; PLANT LOCATION SELECTION; SUITABLE AREAS; MCDM APPROACH; ELECTRE II; SYSTEMS; TECHNOLOGIES; EXTENSION; MODEL; FUEL; Chemistry; Electrochemistry; Energy & Fuels